Dietary intake and visceral adiposity in older adults: The Multiethnic Cohort Adiposity Phenotype study - Melissa A. Merritt; Unhee Lim; Johanna W. Lampe; Tanyaporn Kaenkumchorn; Carol J. Boushey; Lynne R. Wilkens; John A. Shepherd; Thomas Ernst; Loïc Le Marchand (Wiley, 2024)
Abstract Background There are established links between the accumulation of body fat as visceral adipose tissue (VAT) and the risk of developing obesity‐associated metabolic disease. Previous studies have suggested that levels of intake of specific foods and nutrients are associated with VAT accumulation after accounting for total energy intake. Objective This study assessed associations between a priori selected dietary factors on VAT quantified using abdominal magnetic resonance imaging. Methods The cross‐sectional Multiethnic Cohort Adiposity Phenotype Study included n = 395 White, n = 274 Black, n = 269 Native Hawaiian, n = 425 Japanese American and n = 358 Latino participants (mean age = 69 years ± 3 SD). Participants were enrolled stratified on sex, race, ethnicity and body mass index. General linear models were used to estimate the mean VAT area (cm2) for participants categorized into quartiles based on their dietary intake of selected foods/nutrients adjusting for age, sex, racial and ethnic groups, the total percentage fat from whole‐body dual energy X‐ray absorptiometry and total energy. Results There were significant inverse associations with VAT for dietary intake of total vegetables, total fruits (including juice), cereals, whole grains, calcium, copper and dietary fiber (p‐trend ≤0.04). Positive trends were observed for VAT for participants who reported higher intake of potatoes, total fat and saturated fatty acids (SFA) (p‐trend ≤0.02). Foods/nutrients that met the multiple testing significance threshold were total fruits, whole grains, copper, dietary fiber and SFA intake. Conclusions These results highlight foods and nutrients including SFA, total fruit, whole grains, fiber and copper as potential candidates for future research to inform dietary guidelines for the prevention of chronic disease among older adults.